Determination of antibacterial and larvicidal activities of vateria copallifera - Senadeera, S.P.D. (My University, 2010)
Crudeacetoneextracts of leaf, bark, pericarp and seeds of Vateriacopall(terawere evaluated for antibacterialactivity against ten pathogenic microorganisms, Escherichia coli ATCC 25922, Pseudomonasaeruginosa ATCC 27853, Staphylococcu.fJaureus ATCC 25923, Streptococcus faeca/is ATCC 29212, Escherichia coli 0-157, Staphylococcus aureus NCTC4163 and Pseudomonasaeruginosa var erythrogen NCTC 6749, Salmonella typhi, Methicilin resistance staphaureus(MRSA) and Methicilin sensitive staphylococcus aureus (MSSA). All the extracts inhibitedthe growth of five Gram-positivemicroorganisms,Staphylococcusaureus ATCC 25923and Streptc>cc>cl-'Us faecalis ATCC 29212, Staphphylocc>cctl.."i aureus NCTC4163 and Pseudomonasaeruginosa var erythrogen NCTC 6749, Methidlin resistance .vtaphylococcus aureus (MRSA) and Methicilin seUfJitive staphylocoCl-'Usaureus (MSSA). The highest antibacterialactivity with zone of inhibition 20 :f: 0 mm was reported from tlte seeds against MRSAas evident from MIC >0.0]526 mg/ml and MBC> 0.125 mg/m!.The lowest antibacterial activitywas reported from tile pericarp against MRSA with MIC>O.125mg/ml and MBC> 4 mg/mLCommercially available antibiotic discs sulpbametiloxazole trimetltoprim (25 J.lg). ampicilin(10 J.lg),erythromycin (15 J.lg)were used as positive controls. Absolute ethanol was thenegativecontrol with zone of inhibition0 :f: O. Seedextractwhich reportedthe highest antibacterialactivity was subjected to column chromatographyand obtained five fractions. (A, B,C, D, E). Fractions were tested for antibacterial activity and B reported the highest activity. Basedon the current results it can be concluded that parts of tile plant has antibacterial activity, which is as potent as standard antibacterial drugs against some microorganisms, especially againstStaphylococcus aureus. This study also investigatedthe larvicidalpotential of leaf. bark, pericarpand seeds of Valeria copallijera against mosquito larvae Culex quinquefasciatus and Aedes aegypti. The late third instar lmvae were used for larvicidal assay. The highest larval mortalitywas found in seed extract with LCsoandLC90values 465.3 mgll, 661.3 mgll and 915.8 mg/l, 1015.9 mgll against Culex quinquefasciatus and Aedes aegvpti respectively. This is an ecofriendlyapproach for the control of filariasis vector and dengue vector.